Early Childhood Stimulation (ECS) through Play-based teaching to improve the Math skills of Children Aged 5 in Muday Charity Association kindergarten in Addis Ababa. - Assefa, Abera (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2023)
The current study sought to investigate the effect of early childhood stimulation (ECS) through play-based teaching to improve the math skills of children aged 5 at the Muday Charity Association kindergarten in Addis Ababa, Ethiopia. The research was conducted between randomly selected experimental groups (n = 11, 5 years) and control groups (n = 11, 5 years), using two groups of design before and after the test. The results of the study depicted that there was a significant rank difference between the two groups after the intervention was carried out. Moreover, the Mann-Whiny U test result revealed that there were significant differences in post-test results between the Experimental and Control groups on Math skill results, (U=27.50, P=.028). Hence, teachers who are working with early childhood in general and math teachers, in particular, should be aware of the significance of play-based math teaching and should work on adopting different games and materials that align with specific math concepts.